Lateritic soil stabilization by using roadpacker plus [electronic resource] - Goh, Li Lian, 1988- author; Ahmad Safuan A. Rashid, supervisor; Fakulti Kejuruteraan Awam (2014)
Thesis (Sarjana Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2014